Marketing activities of “A Plus Group Ltd.” and overview of RMG sector of Bangladesh - Nadeea, Tazreean Tamiz (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.